Aplikasi Penggunaan Karpet Mulsa Organik Jerami dan Sekam Padi Terhadap Pertumbuhan dan Hasil Paria (Momordica charantina L.) Varietas Lipa F1 di Pakisjaya, Karawang. - Kardiman; Bastaman Syah; Fawzy Muhammad Bayfurqon (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2021)
The plastic problem had become a global problem, which until now there was no right solution to solve it. The agricultural sector in plant cultivation activities from upstream to downstream was quite a lot of plastic waste produced, one of which was the massive use of plastic mulch in horticultural cultivation. Therefore it is necessary to develop the use of mulch with natural materials that are more environmentally friendly. This study aims to determine the effect of the application of mulch based on straw and rice husks on the growth and yield of paria Lipa F1 varieties in Pakisjaya, Karawang. The research was conducted in Telukbuyung Village, Pakisjaya District, Karawang Regency for 3 months from August to November 2020. This study used an experimental method with a Randomized Block Design (RBD) as the environmental design. The treatment given was giving mulch to the cultivation of pariah plants which consisted of 4 levels of treatment (A. Control / No Mulch, B. Black Silver Plastic Mulch, C. Rice Straw Organic Mulch Carpet, D. Organic Rice Husk Mulch Carpet) and repeated as many as 6 times so that there are 24 Trial Units. The results showed that the application of various mulching showed a significant effect on the growth and yield of bitter melon variety of Lipa F1 in Pakisjaya, Karawang. Silver black plastic mulch had the highest average value on observed parameters among other treatments, but the use of organic mulch carpet made from straw and rice husk had the potential as an alternative in mulching in horticultural cultivation.